R&D in a duopoly under incomplete information. (3rd August 2018) - Chatterjee, Rittwik; Chattopadhyay, Srobonti; Kabiraj, Tarun
Abstract: The availability of information about rivals may have a significant impact on a firm's decision about R&D investment. This paper investigates how the R&D incentive of a firm in a Cournot duopoly may depend on information structures. We show that asymmetric information about the rival's cost reduction may enhance the research incentive of each firm compared to the complete‐information case. However, an additional dimension of asymmetry (e.g. the information about whether the rival has invested in R&D or not) will reduce the R&D incentive unambiguously compared to the one‐dimensional asymmetry case.